Pendayagunaan Ekonomi Umat melalui Workshop Optimalisasi Pengumpulan dan Penyaluran Zakat - Khozin, Muhammad; Wilda, Zaidan Rizqia; Budiyono, Alief; Ali, Jauhar (Abdibaraya, 2025)
Based on data from the Central Statistics Agency, Kebumen is the poorest district in Central Java. With the establishment of zakat villages in several villages in Kebumen District, including Sampang Village in Sempor Subdistrict, it is hoped that they can work together with the local government to alleviate poverty. With the designation of Sampang Village as a zakat village by the Ministry of Religious Affairs of the Republic of Indonesia, the KKN Group 1 team from UIN Prof. K.H. Saifuddin Zuhri Purwokerto x UIN K.H. Abdurrahman Wahid Pekalongan organized a workshop on the Optimization of Zakat Management and Utilization Policies with the aim of serving as the initial step for the Zakat Collection Unit in Sampang Village in optimizing policies and managing zakat. The activity was conducted in three stages: preparation, implementation, and evaluation. The preparation stage involved interviews with the head of the Zakat Collection Unit of Sampang Village and preparing the necessary equipment, such as MMT, searching for presenters, and so on. The second stage was the implementation stage, where the material was presented directly by the head of the Religious Affairs Office of the Ministry of Religious Affairs of Sempor Sub-district. The final stage was the evaluation stage, which aimed to evaluate the activities that had been carried out and provide insights for future activities. The event was held at the Sampang Village Hall in Sempor Sub-District, Kebumen Regency. The topics discussed included the definition of zakat, types of zakat, the benefits of zakat from religious, moral, and social perspectives, as well as the recipients of zakat